Control of purple nutsedge (Cyperus rotundus L.) using glyphosate and 2,4-D sodium salt - Ameena, M.; George, Sansamma (Journal of Tropical Agriculture, 2006)
An experiment was conducted to investigate the efficacy of two systemic herbicides, viz., glyphosate and 2,4-D Na salt at varying doses and combinations for the control of purple nutsedge (Cyperus rotundus L). The lowest dose (1.5 kg ai ha-1) of both herbicides gave complete control of shoot growth and there was no re-growth up to six weeks after spraying. Tuber dry weights also showed drastic reduction following herbicide application and glyphosate at 2.0 kg ai ha-1 recorded the least values. Data on tuber germination, however, indicated probable reinfestation, necessitating repeated application or the use of herbicidal mixtures for a complete kill of the weed.